Drinking gall and vinegar: Psalm 69:22: an underestimated intertext in Matt 27:34, 48 - Euler, Alida C. (Zeitschrift für die neutestamentliche Wissenschaft, 2021)
The intertextual play with Psalm 69:22 in Matt 27:34, 48 is an important aspect for adequately understanding Matthew’s crucifixion scene. In Matt 27:34 the Roman soldiers offer Jesus “wine mixed with gall”, which is an allusion to Psalm 69:22a. By acting as the praying-self’s opponents, the Roman soldiers are portrayed as the mockers of Psalm 69:22a. In Matt 27:48, the Jewish authorities offer vinegar to the crucified Jesus, which is a clear allusion to Psalm 69:22b. Therefore, the Jewish authorities are portrayed in parallel to the Roman soldiers. Considering that Matthew refers to Psalm 69:22 not in a selective manner, but in the psalm’s context, the parallel between the Roman soldiers and the Jewish authorities extends to the crucial point in Jewish self-conception of being accused of ἀνομία.
Keywords: Autorität; Juden; Soldat; Römer; anomia; Kreuzigung Jesu; Intertextualität; Bibel / Psalmen; Bibel / Matthäusevangelium